Pre-service Preparation of Elementary School Teachers for Inclusive Education in Northern Mindanao, Philippines - Aranas, Therese June; Cabahug, Ruth (JPAIR Multidisciplinary Research, 2017)
The continuous push for 'ducation for All' suggests that there will be more learners with disability or exceptionality attending inclusive classrooms.  The study attempted to look at how higher education institutions in Northern Mindanao or Region 10 were preparing non-special education elementary school teachers for inclusive education.  Employing qualitative curriculum content analysis, 252 syllabi of the foundational courses in 21 Bachelor of Elementary Education degree programs for non-special education majors were examined to determine how they addressed literature-based inclusion competencies.  The findings are reflective of those in similar studies. One or two introductory theoretical courses in special education were required in preparing elementary school teachers for inclusive education. Analysis revealed few cases of moderate to high coverage of the inclusion competencies in understanding exceptionality, collaboration, inclusive instructional strategies, and inclusive assessment under the professional education courses.  There was a predominantly zero-to-low coverage of the inclusion competencies related to the concept of inclusive education and classroom management.  The limited coverage of literature-based inclusion competencies prompted recommendations for the enhancement of elementary teacher education programs to effectively prepare teachers for inclusive classrooms.
Keywords: Teacher education; inclusive education teaching competencies; curriculum content analysis; Northern Mindanao; Philippines